1967
DOI: 10.2136/sssaj1967.03615995003100020019x
|View full text |Cite
|
Sign up to set email alerts
|

Kaolinization of Biotite as a Result of Coniferous and Deciduous Seedling Growth

Abstract: The rhizosphcric activity of coniferous and deciduous tree seedlings grown for a period of 13 months in sand cultures containing biotite (50 to 2/i) as the only source of K and Mg, effected the transformation of biotite to kaolinite. The identity of the kaolinite was established by means of X-ray diffraction and electron microscope analyses. The effectiveness of the seedlings in producing kaolinite from biotite was in the order: white cedar > hemlock > white pine > white spruce > red oak > hard maple [(Thuja o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
3

Year Published

1976
1976
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 0 publications
1
17
0
3
Order By: Relevance
“…reported that the vermiculitization of phlogopite resulted from an exchange of interlayer K occurring as a consequence of the large depletion of K in close vicinity of the roots. Transformation of biotite and phlogopite to HIV or kaolinite has been also reported (Spyridakis et al 1967).…”
Section: Discussionmentioning
confidence: 91%
“…reported that the vermiculitization of phlogopite resulted from an exchange of interlayer K occurring as a consequence of the large depletion of K in close vicinity of the roots. Transformation of biotite and phlogopite to HIV or kaolinite has been also reported (Spyridakis et al 1967).…”
Section: Discussionmentioning
confidence: 91%
“…This means that biotite has mainly been dissolved by an incongruent phenomenon which corresponds to the partial transformation of biotite into vermiculite. Weathering of phyllosilicates into vermiculite is basically a cation-exchange process which can be accelerated by uptakes of K by plants (Spyridakis et al 1967;Boyle and Voigt 1973;Hinsinger et al 1992) and ECM fungi (Leyval and Berthelin 1991;Paris et al 1995;Glowa et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Podzolization, which is paramount in the pedogenesis of the soils under study, can cause chemical weathering (23)(24)(25)(26). Clay transformation is enhanced by such factors as vegetation cover and microorganisms (27,28). Podzolization has been the subject of much research (29)(30)(31)(32)(33)(34) and podzolic soils are considered to be formed under acidic conditions only.…”
Section: Introductionmentioning
confidence: 99%